Antarctic Genomics. Issue 3 (2004) - Clark, Melody S.; Clarke, Andrew; Cockell, Charles S.; Convey, Peter; Detrich III, H. William; Fraser, Keiron P. P.; Johnston, Ian A.; Methe, Barbara A.; Murray, Alison E.; Peck, Lloyd S.; Römisch, Karin; Rogers, Alex D.
Abstract : With the development of genomic science and its battery of technologies, polar biology stands on the threshold of a revolution, one that will enable the investigation of important questions of unprecedented scope and with extraordinary depth and precision. The exotic organisms of polar ecosystems are ideal candidates for genomic analysis. Through such analyses, it will be possible to learn not only the novel features that enable polar organisms to survive, and indeed thrive, in their extreme environments, but also fundamental biological principles that are common to most, if not all, organisms. This article aims to review recent developments in Antarctic genomics and to demonstrate the global context of such studies.